2013
DOI: 10.3233/jad-130776
|View full text |Cite
|
Sign up to set email alerts
|

Insulin/IGF Signaling-Related Gene Expression in the Brain of a Sporadic Alzheimer's Disease Monkey Model Induced by Intracerebroventricular Injection of Streptozotocin

Abstract: We reported previously that the intracerebroventricular streptozotocin (icv-STZ)-treated cynomolgus monkey showed regionally specific glucose hypometabolism in FDG-PET imaging, similar to that observed in the early stages of sporadic Alzheimer's disease (sAD). However, further pathological analyses of this model at the molecular level are needed to validate it as a feasible model for sAD. Two cynomolgus monkeys were injected with 2 mg/kg STZ into the cerebellomedullary cistern at day 1, 7 and 14. Two control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
(95 reference statements)
2
27
0
Order By: Relevance
“…Streptozotocin (STZ) is a drug toxic for insulin secreting/producing cells and IR (Szkudelski 2001, Kadowaki et al 1984. Similar to what has been found in the human sAD brain, the glucose metabolism was found reduced in 17 of 35 brain areas in the STZ-icv treated rats (Duelli et al 1994) and the activities of glycolytic key enzymes were found markedly decreased (Plaschke and Hoyer 1993) Recently, regionally specific glucose hypometabolism in FDG-PET imaging was found in monkeys 6 and 12 weeks after the STZ-icv treatment (Lee et al 2014;Heo et al 2011). Numerous changes have been found in the insulin/IR signalling cascade in the brain of STZ animal model as reviewed in Table 1.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Streptozotocin (STZ) is a drug toxic for insulin secreting/producing cells and IR (Szkudelski 2001, Kadowaki et al 1984. Similar to what has been found in the human sAD brain, the glucose metabolism was found reduced in 17 of 35 brain areas in the STZ-icv treated rats (Duelli et al 1994) and the activities of glycolytic key enzymes were found markedly decreased (Plaschke and Hoyer 1993) Recently, regionally specific glucose hypometabolism in FDG-PET imaging was found in monkeys 6 and 12 weeks after the STZ-icv treatment (Lee et al 2014;Heo et al 2011). Numerous changes have been found in the insulin/IR signalling cascade in the brain of STZ animal model as reviewed in Table 1.…”
Section: Introductionsupporting
confidence: 62%
“…The progression of decrement in IR protein expression correlated with downregulation of the corresponding gene up to the 3-month time-point after which a magnitude of decrement in the protein level started slowly but persistently to decline in the course of time. Some reports indicate downregulation of IR mRNA in HPC observed as long as 5 months after the STZ-icv treatment (Yang et al 2014;Lee et al 2014) while others (de la did not found significant changes in the HPC 4 weeks after the STZ-icy treatment. The time-course of changes in IDE protein levels in our experiments did not correlate with changes in the corresponding gene as the former did not progressed but showed a tendency of diminishing the magnitude of decrement in a period from 1 to 3 months, after which a persistent decline was observed further on.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In comparison to AD, in VaD, human brain neurotransmitter alterations are mild, e.g., for choline acetyltransferase activity, muscarinic receptor density, serotonin, dopamine, homovanillic acid, dopamine D1-and D2-receptor density, noradrenaline, and gamma aminobutyric acid (GABA), while 5-hydroxyindoleacetic acid (5-HIAA) shows a more pronounced deficiency. This data summarized here agree in principle with more recent conclusions of post-mortem human brain studies and experimental models (Ohara et al 1994;Pimlott et al 2004;Jia et al 2004;Tohgi et al 1996;Chen et al 2013;Lee et al 2014;Niwa et al 2002;Pedrós et al 2014;Knezovic et al 2015;Barilar et al 2015). CSF concentrations of choline were significantly higher in VaD patients compared to AD and controls but did no correlate with mini-mental state examination (MMSE) scores (Jia et al 2004;Tohgi et al 1996).…”
Section: Pathologysupporting
confidence: 92%
“…Widely exploited transgenic animal models of AD (Lithner et al 2011) represent the familial form of AD and do not mimic the sAD condition (Balducci and Forloni 2011). Animal model which develops insulin resistant brain state and glucose hypometabolism following the intracerebroventricular application of a betacytotoxic drug streptozotocin in small rodents and cynomolgus monkey (STZ-icv model), (Agrawal et al 2011;Grünblatt et al 2007;Lannert and Hoyer 1998;Lee et al 2014;Lester-Coll et al 2006;Plaschke and Hoyer 1993;Salkovic-Petrisic et al 2006), shares similarities with the human sAD condition (Lannert and Hoyer 1998) since insulin resistant brain state was found postmortem in sAD patients (Correia et al 2011;de la Monte and Wands 2005;Frölich et al 1998). Additionally, STZ-icv model demonstrates also cognitive deficits (Mayer et al 1990;Lannert and Hoyer 1998) and decrement in cerebral cholinergic transmission (Blokland and Jolles 1993;Hellweg et al 1992), as well as other features of chronic neurodegeneration like oxidative stress and neuroinflammation (Saxena et al 2011;Sharma and Gupta 2001) and in particular tau protein hyperphosphorylation (Grünblatt et al 2007;Deng et al 2009;Liu et al 2014;Peng et al 2013), pathological Aβ accumulation (Shingo et al 2013) and cerebral amyloid angiopathy (Salkovic-Petrisic et al 2006, 2011.…”
Section: Introductionmentioning
confidence: 99%